The Study of Religious Beliefs in the Contemporary Northeastern Thai Folk Songs - Meesong, Kanchit; Thawinkham, Chutikarn (Journal of Paramita, 2021)
The study of religious beliefs appears in the contemporary northeastern Thai folk songs. The study emphasized on types and unique religious beliefs of northeastern Thai people that occurred in the popular songs which are wildly known by Thai people. The study showed that the types of religious beliefs that were found in contemporary folk songs include the beliefs of supernatural power, sin and merit and the karma (the result of bad actions). Furthermore, the concepts of religious beliefs had directly influenced the local customary taboos which are the ways of life of northeastern people in Thailand.